Investigating the possible role of fatty acid binding proteins (FABPs) in nociceptive pain processing - Brailsford, Louis Alex (2017)
The transient receptor potential vanilloid 1 (TRPV1) channel protein is activated by lipid metabolites synthesized in the cytosol of nociceptors in response to noxious stimulation. Lipid species include the endocannabinoid anandamide (AEA) and the linoleic acid metabolite 13 (S) hydroxyoctadecadienoic acid (HODE) which act as endogenous TRPV1 ligands (endovanilloids) by evoking TRPV1 mediated Ca2+ entry. Members of the fatty acid binding protein (FABP) family have been widely reported to act as intracellular lipid binding proteins for hydrophobic lipid species in aqueous cytosolic environments. The aim of this thesis was to identify which FABP isotypes could solubilize then shuttle AEA and 13(S)HODE to TRPV1 during nociception. Inhibiting FABP mediated transportation of endovanilloids could represent an alternative approach to analgesia by indirectly antagonizing TRPV1 activity during nociception while avoiding the widely reported negative side effects of direct antagonism. For the first time, it was found that FABP isoforms 5, 7 and 8 were expressed in rat dorsal root ganglia cell preparations. Furthermore, subsequent cell free competitive binding assays confirmed that FABP5, 7 and 8 could all physically bind to AEA and 13(S)HODE albeit with variable affinities. The ability of FABP 5, 7 and 8 to physically associate with TRPV1 and therefore deliver AEA was then assessed in live mammalian cell lines transfected with plasmid DNA constructs expressing recombinant TRPV1 and FABPs. Physical interactions between TRPV1 and FABP5, 7 and 8 were observed in COS-7 cells examined by fluorescence microscopy. However, when increases in intracellular Ca2+ levels were measured in COS-7 cells co-expressing TRPV1 and FABP, in response to treatment with 1µM AEA, the magnitude of AEA evoked Ca2+ influxes were not significantly different to those observed in COS-7 cells not co-expressing the FABPs. This suggested that the FABPs did not functionally associate with TRPV1 and did not deliver AEA to TRPV1 receptors. In conclusion, data in thesis showed that the FABP isoforms expressed in DRG cell preparations could physically associate with lipid species reported to activate TRPV1 during nociception.